2019
DOI: 10.1016/j.surg.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery in liver surgery decreases postoperative outpatient use of opioids

Abstract: Background: Pathways of Enhanced Recovery in Liver Surgery (ERILS) decrease inpatient opioid use, however, there is little existing data regarding their effect on discharge prescriptions and post-discharge opioid intake. Methods: For consecutive patients undergoing liver resection from 2011-2018, clinicopathologic factors were compared between patients exposed to ERILS and traditional pathways. Multivariable analysis was used to determine factors predictive for traditional opioid use at the first postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…Implementation of the ERATS protocol resulted in a drastic reduction of new persistent opioid use without adversely affecting outcomes [ 13 ]. Similar longitudinal results have been reported in liver surgery [ 14 ], indicating potentially unrealized benefits of ERAS protocols that extend beyond discharge.…”
Section: Perioperative Protocols/clinical Pathwayssupporting
confidence: 81%
“…Implementation of the ERATS protocol resulted in a drastic reduction of new persistent opioid use without adversely affecting outcomes [ 13 ]. Similar longitudinal results have been reported in liver surgery [ 14 ], indicating potentially unrealized benefits of ERAS protocols that extend beyond discharge.…”
Section: Perioperative Protocols/clinical Pathwayssupporting
confidence: 81%
“…Currently, enhanced recovery pathways are an advantageous contemporary perioperative care model for hepatectomy patients with benefits that include reduced LOS, decreased morbidity, decreased opioid use, and earlier recovery to baseline [ [3] , [4] , [5] , 23 , 24 ]. However, enhanced recovery pathways are often singular for all patients regardless of operative complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Discharge prescriptions <200 mg OME were not associated with increased refill rates, as would be expected by nterventions reported by others at ours and other institutions have shown that implementation of opioid education and prescribing guidelines can effectively reduce the quantity of opioid prescribed for patients undergoing surgery for various indications. [17][18][19][20][21] Such interventions have centered on implementation of education for prescribers, evidence-based prescribing guidelines, and standardized patient instructions. 17,18,20,21 Implementation of enhanced recovery pathways that encompass opioid-sparing techniques has been widely…”
Section: Discussionmentioning
confidence: 99%